Armstrong relations and strong dependencies - Thi, Vũ Đức (Journal of Computer Science and Cybernetics, 2016)
In this paper, the concept of strong scheme is introduced. We prove that the membership problem for strong dependencies is solved by an algorithm in polynomial time. We give a necessary and sufficient condition for a relation to be Armstrong relation of a given strong scheme.